2021
DOI: 10.1371/journal.pone.0248964
|View full text |Cite
|
Sign up to set email alerts
|

Systemic metabolite profiling reveals sexual dimorphism of AIBP control of metabolism in mice

Abstract: Emerging studies indicate that APOA-I binding protein (AIBP) is a secreted protein and functions extracellularly to promote cellular cholesterol efflux, thereby disrupting lipid rafts on the plasma membrane. AIBP is also present in the mitochondria and acts as an epimerase, facilitating the repair of dysfunctional hydrated NAD(P)H, known as NAD(P)H(X). Importantly, AIBP deficiency contributes to lethal neurometabolic disorder, reminiscent of the Leigh syndrome in humans. Whereas cyclic NADPHX production is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…NAD levels are also reduced in the NAXE knockout heart, which is consistent with our findings of metabolites in the plasma [ 30 ]. The reduced NAD levels are probably the cause of the red, flaky skin of Pellagra disease in patients with NAXE mutation [ 13 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…NAD levels are also reduced in the NAXE knockout heart, which is consistent with our findings of metabolites in the plasma [ 30 ]. The reduced NAD levels are probably the cause of the red, flaky skin of Pellagra disease in patients with NAXE mutation [ 13 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, in contrast to human fibroblasts or other organisms, absence of NAXE in murine cardiac tissues appears to selectively perturb NADHX but not NADPHX repair. While NAXE knockout does not significantly change cardiac NAD or NADH levels, the NAD levels trend lower, which is consistent with the NAD content in plasma [ 30 ]. We further assessed the effect of NAXE on NAD levels in HUVECs.…”
Section: Resultssupporting
confidence: 67%
“…Schneider et al [ 36 ] found that AIBP −/− /LDLR −/− mice fed a high-cholesterol, high-fat diet exhibited exacerbated weight gain, liver steatosis, glucose intolerance, hypercholesterolemia, hypertriglyceridemia, and larger atherosclerotic lesions compared to LDLR −/− mice. In addition, a report examining systemic metabolites in plasma samples from AIBP knockout mice indicated that AIBP may play an important role in regulating cellular metabolism [ 39 ]. In the present study, we used bone marrow transplantation (BMT) to transplant bone marrow from AIBP knockout mice or their wild-type littermate controls into LDL receptor knockout mice to construct AIBP WT /LDLR −/− and AIBP ΔBMK /LDLR −/− mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities in the clinical presentation between patients with NAXE or NAXD deficiency provide robust evidence in support of NAD(P)HX accumulation and/or NAD(P)H depletion being the common causal factor involved in the pathogenesis and of a minor implication, if any, for a secondary role reported for NAXE as a secreted Apolipoprotein A‐1 binding protein that is involved in cholesterol efflux, angiogenesis, and atherosclerosis. Naxe knockout mice have so far been analysed mostly with a focus on these latter secondary functions, 7 , 8 , 32 and it is unclear whether these mice have any neurological impairment. Given the moonlighting functions of NAXE and the essential function of NAXD in NAD(P)HX repair, developing a Naxd deficient mouse model seems like an inevitable next step to progress in whole organism disease modelling of NAD(P)HX repair deficiency and ongoing work is under way to reach this goal.…”
Section: Future Research Requirementsmentioning
confidence: 99%